The Impact of COVID-19 on Breast Reconstruction: A Nationwide Analysis Utilizing NSQIP - Pires, Giovanna R.; Moss, Whitney D.; Sudduth, Jack D.; Marquez, Jessica L.; Mills, Andrew; Samlowski, Erika; Clinker, Christopher; Eddington, Devin; Hobson, Greg (Journal of Reconstructive Microsurgery Open, 2023)
Background The coronavirus disease 2019 (COVID-19) global pandemic prompted an unprecedented contraction in surgical volume. This utilizes the American College of Surgeons' National Surgical Quality Improvement Program (NSQIP) database to assess the impact of COVID-19 on breast reconstruction surgery volume and quality throughout 2020.Methods The NSQIP database was utilized to gather data from 2015 to 2020. We provide descriptive statistics in the form of mean (standard deviation), median (interquartile range), and range for continuous variables and counts (%) for categorical variables. A Kruskal–Wallis test was used to compare average age and a chi-squared test was used to compare other demographic categorical variables from 2019 to 2020.Results Breast reconstruction procedures decreased by 27% in Q2 2020 compared to Q2 of 2019. Immediate tissue-expander-based reconstruction was the only type of reconstruction that increased in comparison to Q2 2019 values (53.5 vs. 41.1%, p < 0.001). Rates of delayed direct to implant reconstruction was decreased (12.8 vs. 17.5%, p < 0.001) and free flap-based breast reconstruction decreased, including immediate free flap reconstruction (5.3 vs. 9%, p < 0.001) and delayed free flap reconstruction (5.7 vs. 9.1%, p < 0.001). Immediate direct to implant reconstruction rates were unchanged. In terms of surgical quality, there were no statistically significant increases in postoperative complications, readmissions, or reoperations.Conclusion Breast reconstruction surgery was heavily impacted in Q2 of 2020 with a 27% decrease in total surgical volume. There was an increase in immediate tissue-expander-based reconstruction and decrease in rates of both direct to implant and free-flap based reconstruction. Surgical quality and outcomes remained unchanged through the pandemic.
Keywords: reconstruction; breast; quality; volume; COVID-19